2016
DOI: 10.1111/trf.13860
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Middle East respiratory syndrome coronavirus (MERS‐CoV) in plasma products using a riboflavin‐based and ultraviolet light‐based photochemical treatment

Abstract: Riboflavin and UV light effectively reduced the titer of MERS-CoV in human plasma products to below the limit of detection, suggesting that the treatment process may reduce the risk of transfusion transmission of MERS-CoV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 17 publications
(27 reference statements)
3
117
1
2
Order By: Relevance
“…A recent study investigated the inactivation of MERS-CoV in plasma using riboflavin and UV light. 47 The study showed a reduction of at least 4.07 and at least 4.42 log in viral titers for pooled and individual donor plasma, respectively. However, passaging experiments after pathogen reduction were not conducted, so complete inactivation of all infectious particles cannot be taken for granted.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study investigated the inactivation of MERS-CoV in plasma using riboflavin and UV light. 47 The study showed a reduction of at least 4.07 and at least 4.42 log in viral titers for pooled and individual donor plasma, respectively. However, passaging experiments after pathogen reduction were not conducted, so complete inactivation of all infectious particles cannot be taken for granted.…”
Section: Discussionmentioning
confidence: 83%
“…It is documented that VB2 significantly improves serum and the histological parameters of hepatocellular damage and neutrophil infiltration following liver ischemia in mice [17]. Recently, many studies have also demonstrated that irradiated riboflavin protects the cisplatin-induced oxidative stress-mediated hepatotoxicity and nephrotoxicity in rodent based studies [47][48][49][50]. Furthermore, VB2 and UV light together were able to reduce the titer of MERS-CoV in human plasma products to a non-detecting level suggesting that the combination may lower the risk of transfusion transmission of MERS-CoV [51].…”
Section: Discussionmentioning
confidence: 98%
“…The infectious titer of virus did not show any significant reduction after 25 cycles of thawing and freezing [44]. After the outbreak of SARS and MERS, a few studies investigated pathogen inactivation/reduction technologies (PRTs) based on in-house or commercial methods with the aim to decrease or completely eradicate the potential risk of transmission of coronaviruses via blood products or blood derivatives [45][46][47][48][49][50][51][52][53][54]. These studies are summarized in Table 1.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%
“…Illumination with different wavelengths also influenced activities of SARS and MERS virus in blood. Ultraviolet (UV)-A [46,47,51]and UV-B light [54] in the presence of amotosalen or riboflavin could inactivate the pathogens' nucleic acids, whereas a third PRT method uses UV-C light only [45,48]. These commercial systems could reduce the activities of SARS and MERS virus in plasma or platelet concentrates to different degrees.…”
Section: Inactivation Of Coronavirus In Blood Productsmentioning
confidence: 99%